Handbook of materials failure analysis with case studies from the aerospace and automotive industries - Makhlouf, Abdel Salam Hamdy; Aliofkhazraei, Mahmood (Butterworth-Heinemann is an imprint of Elsevier, 2015)
Handbook of Materials Failure Analysis: With Case Studies from the Aerospace and Automotive Industries provides a thorough understanding of the reasons materials fail in certain situations, covering important scenarios, including material defects, mechanical failure as a result of improper design, corrosion, surface fracture, and other environmental causes. The book begins with a general overview of materials failure analysis and its importance, and then logically proceeds from a discussion of the failure analysis process, types of failure analysis, and specific tools and techniques, to c.